The Influence Of Brand Loyalty, Cross-Channel Search, Channel Price Advantage, Channel Satisfaction, Risk Perception On Shopee Channel Selection Intention Channel Selection Intention Shopee (Case Study Of Maybelline Lipstick Products) In Padang City.: PENGARUH BRAND LOYATY, CROSS-CHANNEL SEARCHING, CHANNEL PRICE ADVANTAGE, CHANNEL SATISFACTION, PERCEIVED RISK TERHADAP CHANNEL SELECTION INTENTION SHOPEE (STUDI KASUS PRODUK LIPSTIK MAYBELLINE) DI KOTA PADANG - Annisa Safira Marsal; Mike Yolanda (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research aims to examine the influence of Brand Loyalty, Cross-Channel Search, Channel Price Advantage, Channel Satisfaction, Perceived Risk on Shopee Channel Selection Intention (Case Study of Maybelline Lipstick Products) in Padang City. Data was collected through online distribution of questionnaires from 300 respondents. The research method used is quantitative with data analysis using Smart PLS and the boostsrap technique. The research results show that (1) Brand Loyalty has an influence on Channel Selection Intention. (2) Cross-Channel Search has no effect on Channel Selection Intention. (3) Channel Satisfaction has no effect on Channel Selection Intention (4) Channel Price Advantage has no effect on Channel Selection Intention. (5) Perceived Risk influences Channel Selection Intention. These findings provide insight into how Brand Loyalty, Cross Channel Searching, Channel Price Advantage, Channel Satisfaction, Perceived Risk influence Channel Selection Intention.